Lower urinary tract symptoms suggestive of benign prostatic hyperplasia among Ghanaian men: a hospital-based cross-sectional prospective study - Kenneth, Aboah; Francis, Agyemang-Yeboah; Christian, Gyase-Sarpong Kofi; Ferguson, Laing Edwin; Emmanuel, Acheampong; Benjamin, Twumasi Frimpong; George, Amoah; Emmanuella, Batu Nsenbah; Portia, Adutwumwaah Asamoah (International Journal of Research in Medical Sciences, 2016)
Background: Lower urinary tract symptoms (LUTS) of benign prostatic hyperplasia (BPH) are common in the elderly. This study sought to determine the prevalence of LUTS among patients visiting the urology clinic at Komfo Anokye Teaching Hospital, Kumasi, Ghana and to explore its presentation patterns. Methods: Simple randomized sampling technique was used to recruit 225 subjects with a mean age of 67.96±14.57 (range=40-100years) in a prospective cross-sectional study. LUTS related characteristics and international prostate symptom score (IPSS) questionnaire were employed to obtain relevant data. Results: The average IPSS of the studied participants was 17.52±7.83. Based on the IPSS, the prevalence of LUTS suggestive of BPH was 88.89%. Bladder storage symptoms were also recorded at 88.59% whilst prostate enlargement based on digital rectal examination (DRE) was 60.4% among the studied subjects. PSA levels ≥4.0ng/ml gave a prevalence of 81.5%. The prevalence of prostate enlargement defined as PSA ≥1.5ng/ml was 85.23% among the studied subjects whilst 63.11% of the subjects examined had troublesome LUTS. Urgency was the most predominantly reported LUTS (93.3%) among the subjects studied. Conclusions: This study has clearly shown that, the most prevalent urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia were bladder storage symptoms and urgency. These symptoms when present clinically therefore, suggest benign prostatic hyperplasia and that the prevalence estimates of LUTS in older men are relatively higher at diagnosis.